Optimizing Wellness in Chronic Obstructive Pulmonary Disease - Roger S Goldstein; Dina Brooks; Gordon T Ford (Canadian Respiratory Journal)
Optimizing wellness in chronic obstructive pulmonary disease (COPD) is an emerging theme, in response to the substantial burden of COPD among Canadians. Population surveillance, from the Public Health Agency of Canada, as well as from international initiatives, such as the Burden of Obstructive Lung Disease (BOLD) study, has revealed the prevalence and regional disparities of a condition in which mortality, morbidity and health care resource use often reflect what was happening in the population more than 20 years previously. As COPD emerges to be an important women’s health issue, it raises questions as to how female mortality from COPD can rise at double the rate of breast cancer, why the COPD patient population is still predominantly male and whether women experience breathlessness differently than men.